Corneal Perforation as a Rare and Late Manifestation of Choroidal Melanoma - Berger, Tim; Flockerzi, Fidelis; Löw, Ursula; Flockerzi, Elias; Aljundi, Wissam; Abdin, Alaadin; Daas, Loay; Seitz, Berthold (Klinische Monatsblätter für Augenheilkunde, 2023)
Purpose To report a case of corneal perforation as a rare and late manifestation of choroidal melanoma and to highlight the major histopathological findings of this unusual combined clinical presentation.Methods A 74-year-old male patient presented to our department due to corneal perforation of the right eye with the absence of light perception for 6 months. The intraocular pressure was hard on palpation. Because of the protracted finding and reduced visual prognosis, primary enucleation was performed.Results The histopathological examination revealed choroidal melanoma with epithelioid and spindle cell components at the posterior pole, which was positive for Melan-A, Human Melanoma Black 45 (HMB45), BAP1, and SOX10. The anterior segment showed complete anterior chamber hemorrhage and blood remnants in the trabecular meshwork. The cornea displayed diffuse blood staining with hemosiderin and hemosiderin-loaded macrophages and keratocytes. No inflammatory cells were present near the corneal perforation, which had a width of 3 mm. Intraocular heterotopic ossification was indicative of a long-standing condition. Postoperative cancer staging was normal.Conclusion Corneal perforation should be considered as a very rare and late manifestation of advanced choroidal melanoma and may result from interaction between intraocular hemorrhage, elevated IOP, and its secondary signs such as corneal blood staining.
Keywords: cornea; corneal perforation; corneal blood staining; choroidal melanoma; melanoma